An Economic Study of the Consumption Expenditure Function on White Meat (A Case Study of Al-Bayda Municipality) - Khairia A H Sehib; Husniyah Abdullah Mohammed; Salha Muftah Abdulqader Ahwaiti (Journal of Libyan Academy Bani Walid, 2025)
Food commodities are a crucial component of achieving food security, and the consumer expenditure of Libyan households on these goods represents an important indicator of their economic capacity. Therefore, analyzing expenditure elasticity is essential for understanding how dietary consumption patterns respond to economic changes, which supports planning efforts aimed at achieving local self-sufficiency. This study examines the determinants of expenditure on white meat as a primary protein source in order to assess its importance and role within the Libyan household food basket under current conditions. Its significance lies in analyzing the demand function for consumer expenditure on white meat, given its role as a vital animal protein commodity in Libya. A descriptive and quantitative analytical approach was adopted, based on data collected from a sample of 195 households in the city of Al-Bayda during 2024. Descriptive analysis showed that 73% of households perceived the price of white meat to be high, leading 90% of them to reduce the quantities consumed. Using the double-logarithmic demand function model, the study found that consumption elasticity was 0.47. Demand was positively affected by the price of substitute goods, household size, the educational level of the household head, and income. The results indicated that white meat is classified as a necessity, as reflected in an income elasticity of 0.37 Furthermore, analysis of the expenditure function confirmed that 51% of the change in expenditure results from changes in income, with the middle-income group recording the highest income elasticity of consumption at 0.49. The study recommends strengthening regulatory oversight of markets and increasing local production in order to achieve self-sufficiency.